Analysis of Extractions done in primary teeth by UG students in different age groups - Immanuel, Jeswin; Dinesh, Dinesh (Journal of Neonatal Surgery, 2024)
Introduction: The extraction of primary teeth represents a fundamental procedure within the realm of dentistry, bearing a unique significance as both a clinical and pedagogical practice. This article delves into the intricate domain of extracting primary teeth, placing a particular lens on the endeavours undertaken by undergraduate (UG) dental students Materials and method: Dental records were screened for patients aged under 18 years who had undergone primary tooth extraction in private dental college. Discussion: The reasons for extracted primary teeth varied among different age groups. However, extraction due to dental caries and its sequelae was remarkable for all age groups, with the highest number being in the age group 7–9 years, particularly the second primary molars, indicating the high incidence of dental caries AIM:Aim of the study is analysis of extraction done in primary teeth by UG students in different age groups